Ability in diagnosing equipment faults: Contribution of students practical intelligence. - Zol Bahri, Razali, Dr.; Trevelyan, James P. (Taylor's University, Kuala Lumpur, 2013)
Proceedings of the International Engineering and Technology Education Conference (IETEC) 2011 was organized by Taylor's University, Kuala Lumpur, Malaysia with collaboration between Central Queensland University, Australia, Universiti Teknologi Malaysia (UTM) and Universiti Tun Hussein Onn (UTHM), 16th - 19th January 2011 at Kuala Lumpur, Malaysia.